Doxorubicin‐loaded poly(ε‐caprolactone)‐Pluronic micelle for targeted therapy of esophageal cancer. Issue 11 (6th September 2018) - Dai, Shujun; Ye, Zhimin; Wang, Fangzheng; Yan, Fengqin; Wang, Lei; Fang, Jun; Wang, Zhun; Fu, Zhenfu
Abstract: There is still lack of effective treatment of esophageal cancer, and it is urgently necessary to develop a new programs to treat this disease. More and more evidence suggests that the combination of 2 or more treatment strategies can enhance the antitumor activity in cancer treatment. We have established a new therapeutic strategy that combines doxorubicin‐loaded poly(ε‐caprolactone) (PCL)‐Pluronic micelles and miR‐34a to better combat esophageal cancer. Doxorubicin was loaded into PCL‐Pluronic micelle to achieve better uptake. Confocal microscopy was used to assess in vitro cellular uptake of PCL‐Pluronic micelle. Finally, the in vivo effect of this new combination therapy strategy was also studied. The results showed that PCL‐Plannick micelles significantly enhanced the uptake of doxorubicin in esophageal cancer cells in vitro, thereby improving the accumulation of doxorubicin in the cells. In vitro and in vivo combination of doxorubicin‐loaded PCL‐Pluronic micelles and miR‐34a, achieving a significantly synergistic therapeutic effect over the corresponding single treatment. These results suggested that the combinational therapy based on doxorubicin‐loaded PCL‐Pluronic micelle and miR‐34a may provide a reasonable strategy for improving the outcome of esophageal cancer treatment. Abstract : There is still lack of effective treatment of esophageal cancer, and it is urgently necessary to develop a new programs to treat this disease. The combinational therapy based on doxorubicin‐loaded poly(ε‐caprolactone)‐Pluronic micelle and miR‐34a may provide a reasonable strategy for improving the outcome of esophageal cancer treatment.